1993
DOI: 10.1017/s0142716400010687
|View full text |Cite
|
Sign up to set email alerts
|

The metalinguistic benefits of limited contact with a second language

Abstract: This study examined whether the often-reported metalinguistic benefits of childhood bilingualism extend to children whose experience with a second language is considerably more limited, and if so, whether this metalinguistic advantage flows on to reading acquisition. Its purpose was to provide direct evidence of a causal role for metalinguistic awareness in reading acquisition. The study focused on the developing word awareness skills of two groups of preparatory and grade 1 children: one group was strictly mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
97
0
6

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(111 citation statements)
references
References 52 publications
8
97
0
6
Order By: Relevance
“…This conclusion was later repeated in many studies with different language groups and evaluation methods, such as in the tasks of word segmentation (word count) and word judgment. Yelland (1993) found that even English children aged five to seven, after studying Italian one hour a week lasting for six months, performed better than English monolinguals in the tasks of word segmentation and words judgment, which was confirmed by Min's study (2009).…”
Section: The Performance Of Word Awareness Promotionmentioning
confidence: 59%
See 2 more Smart Citations
“…This conclusion was later repeated in many studies with different language groups and evaluation methods, such as in the tasks of word segmentation (word count) and word judgment. Yelland (1993) found that even English children aged five to seven, after studying Italian one hour a week lasting for six months, performed better than English monolinguals in the tasks of word segmentation and words judgment, which was confirmed by Min's study (2009).…”
Section: The Performance Of Word Awareness Promotionmentioning
confidence: 59%
“…), independent of the features of the signified , namely the arbitrary nature between words and the signified (Yelland, 1993).…”
Section: Interpretation Mechanism Of Word Awareness Promotionmentioning
confidence: 99%
See 1 more Smart Citation
“…Son diversos los trabajos, en tareas comunicativas y no comunicativas, que muestran un incremento del habla privada cuando el/la niño/a encuentra conflictos o dificultades en el desarrollo de una tarea (e.g., Díaz et al, 1991;Fernyhough y Fradley, 2005;Montero y De Dios, 2006;San Martín et al, 2011;Varenne y Beaudichon, 1996). La consideración del bilingüismo como situación que favorece el conflicto es algo reseñado a nivel de investigación (Bialystok, 2001(Bialystok, , 2004Yelland et al, 1993). Ello puede resultar favorecedor de la activación de ciertos procesos cognitivos reflexivos, en este caso evidentes por la mayor emergencia del habla privada en la condición de bilingüismo moderado a los seis años.…”
Section: Discussionunclassified
“…Si bien inicialmente el bilingüismo se consideraba una potencial fuente de distorsión psicológica (BIE Luxembourg Conference, 1928), el grueso de la investigación realizada hasta la fecha muestra que la actuación lingüística de los bilingües y monolingües se sitúa en niveles equivalentes, planteándose que la condición de bilingüismo puede favorecer ciertos aspectos del desarrollo metalingüístico y metacognitivo (Meisel, 2004). Bialystok (2001Bialystok ( , 2004) muestra, de manera particular, los efectos favorecedores del bilingüismo en la toma de conciencia metalingüística tal y como también indicaban Yelland, Pollard y Mercuri (1993), en relación a la toma de conciencia del significado de las palabras. En el terreno del desarrollo comunicativo, algunos estudios sugieren que la condición de bilingüismo plantea un conflicto cognitivo que influencia de manera diferencial a bilingües y monolingües .…”
Section: Introductionunclassified